Understanding Surface and Interfacial Chemistry in Functional Nanomaterials via Solid‐State NMR. Issue 14 (1st March 2017) - Marchetti, Alessandro; Chen, Juner; Pang, Zhenfeng; Li, Shenhui; Ling, Daishun; Deng, Feng; Kong, Xueqian
Abstract : Surface and interfacial chemistry is of fundamental importance in functional nanomaterials applied in catalysis, energy storage and conversion, medicine, and other nanotechnologies. It has been a perpetual challenge for the scientific community to get an accurate and comprehensive picture of the structures, dynamics, and interactions at interfaces. Here, some recent examples in the major disciplines of nanomaterials are selected (e.g., nanoporous materials, battery materials, nanocrystals and quantum dots, supramolecular assemblies, drug‐delivery systems, ionomers, and graphite oxides) and it is shown how interfacial chemistry can be addressed through the perspective of solid‐state NMR characterization techniques. Abstract : Surface and interfacial chemistry is of fundamental importance in functional nanomaterials. It has been a perpetual challenge to get an accurate and comprehensive picture of structures, dynamics, and interactions. Through various recent examples in the major disciplines of nanomaterials, it is shown how interfacial chemistry can be addressed through the perspective of solid‐state NMR characterization techniques.